Hepatitis C virus cure does not impact kidney function decline in HIV co-infected patients. (27th March 2018) - Rossi, Carmine; Saeed, Sahar; Cox, Joseph; Vachon, Marie-Louise; Martel-laferrière, Valérie; Walmsley, Sharon L.; Cooper, Curtis; Gill, M. John; Hull, Mark; Moodie, Erica E.M.; Klein, Marina B.
Abstract : Objective: To examine the impact of sustained virologic response (SVR) and illicit (injection and noninjection) drug use on kidney function among hepatitis C virus (HCV) and HIV co-infected individuals. Design: Longitudinal observational cohort study of HCV-HIV co-infected patients. Methods: Data from 1631 patients enrolled in the Canadian Co-Infection Cohort between 2003 and 2016 were analyzed. Patients who achieved SVR were matched 1 : 2 with chronically infected patients using time-dependent propensity scores. Linear regression with generalized estimating equations was used to model differences in estimated glomerular filtration rates (eGFR) between chronic HCV-infected patients and those achieving SVR. The relationship between illicit drug use and eGFR was explored in patients who achieved SVR. Results: We identified 384 co-infected patients who achieved SVR (53% treated with interferon-free antiviral regimens) and 768 propensity-score matched patients with chronic HCV infection. Most patients were men (78%) and white (87%), with a median age of 51 years (interquartile range: 45–56). During 1767 person-years of follow-up, 4041 eGFR measurements were available for analysis. Annual rates of decline in eGFR were similar between patients with SVR [−1.32 (ml/min per 1.73 m 2 )/year, 95% confidence interval (CI) −1.75 to −0.90] and chronic infection [−1.19 (ml/min per 1.73 m 2 ) per year, 95% CI −1.55 to −0.84]. Among SVR patients, recent injection cocaine use was associated with rapid eGFR decline [−2.16 (ml/min per 1.73 m 2 )/year, 95% CI −4.17 to −0.16]. Conclusion: SVR did not reduce the rate of kidney function decline among HCV–HIV co-infected patients. Increased risk of chronic kidney disease in co-infection may not be related to persistent HCV replication but to ongoing injection cocaine use. Abstract : Supplemental Digital Content is available in the text